Thorax development in children from the nursery-schools in Bialystok - Szewko-Szwaykowska, Irena; Jelisiejew, Tamara (Anthropological Review, 1976)
Results on the thorax development of children aged 3 to 8 years. from the nursery schools of Bialystok are reported. Research concerned 431 children (228 boys and 203 girls). The behaviour of the averages of body height, length and breadth, the indicators of body build annual increment in the individual groups of age is analyzed. Analysis of the arithmetical averages proved that the largest differences in body build between girls occur between the 5th and 6th year of age. The largest yearly increments of the examined characteristics were noted in the boys between the 5th aud 6th year of age; on the other hand, the annual increments of those characteristics in the girls occured irregularly. The results obtained are compared with those of other Polish authors.